Mediating effect of ethical leadership on the relationship between personality factors, group norm and counterproductive work behaviour in Nigeria - Amin, Sani Ibrahim (2018)
The success of any organization depends on the behaviour exhibited by its employees. To achieve this, positive ethics value are needed to discontinue negative behaviour within the organization.In view of the foregoing , this study investigated the mediating role of ethical leadership in shaping the relationship between personality factors, group norm and counterproductive work behaviour. This research is using quantitative methodology.Multi-stage cluster sampling technique was used to select 375 academic and non-academics from three public universities located in north-western part of Nigeria that participated in the study. Data of the analysis generated from using Smart PLS 2.0 M3 software to ensure the ascertain internal consistency reliability and discriminant validity of variables. The findings indicate that four out of five dimensions of personality factors (i.e., perceived extraversion, perceived consciousness, perceived agreeableness, and perceived neurotiscm) were found to positively influence counterproductive work behavior. In contrast, perceived openness and group norm were found not to influence counterproductive work behavior. On the relationship between personality factors and ethical leadership, results revealed a positive significant relationship between perceived extraversion, openness and consciousness. Negative relationship between agreeableness, neurotiscm and ethical leadership was found. Similarly, perceived group norm was found to be positively related to ethical leadership. Ethical leadership was found to positively influence counterproductive work behavior. On mediating effect, ethical leadership was found to mediate the relationship between perceived group norm and counterproductive work bahviour while ethical leadership did not mediate the relationship between personality factors and counterproductive work behaviour. In view of the findings, contribution, limitations and conclusion were drawn. The study recommended a novel comprehension of a precedent of the future in order to enhance the counterproductive work behavior in other sector in the short and long runs.